Strategic Management of Inclusive Educational Leadership in Teacher Career Development - Unzilah Khomairohtusshiyamah; Halimahtus Sa’diyah; Rifka Jannatul Firdausiah; Maulidatul Adzimah; Siti Aviatun Hasanah; M Aqil Fahmi Sanjani; Zohaib Hassan Sain (Early Childhood Development Gazette, 2025)
This study aims to analyze the role of strategic management in inclusive educational leadership as an effort to support teacher career development. The study focuses on how principals, as strategic leaders, are able to design, implement, and evaluate inclusive policies that impact teacher competency and professionalism. The research method used was a descriptive qualitative approach through in-depth interviews, observations, and documentation studies in several inclusive schools. The results indicate that inclusive educational leadership based on strategic management can create a collaborative work culture, increase teacher motivation, and expand access to professional development programs. Effective strategies include ongoing career planning, individualized needs-based training, and support for a fair reward system. The implications of this study confirm that the application of strategic management in inclusive leadership not only strengthens teacher capacity but also builds an adaptive, participatory, and equitable education system for all parties within the school environment.